IDENTIFIKASI TITIK KEMACETAN DI KECAMATAN PONTIANAK UTARA, PONTIANAK BARAT DAN PONTIANAK KOTA - Darmawan, Edo; Mayuni, Siti; Sulandari, Eti (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2014)
Growth and development issues impact on the city traffic system. The impact is related to the effect of road capacity and traffic volume, which can cause traffic congestion problem. Of the three sub-districts that were examined, namely North Pontianak, West Pontianak and Pontianak City and there are eight points of congestion, and 3 of them are experiencing congestion are Khatulistiwa Road, the intersection of  Suwignyo Road-  Husein Hamzah Road - Martadinata Road - H. Rais. A. Rahman Road and the intersection of Putri Candramidi Road - Sultan Syarif Abdurrahman Road - Sultan Syahrir Road. The purpose of this paper is to identify and analyze the traffic problems in the form of the factors that cause congestion in the District of North Pontianak, West and City so as to propose treatment plans and actions that can be done to address the problem of traffic congestion. In this study, data were obtained by conducting a survey of traffic volume at peak hours only in 06:00 - 09:00 am for the morning, at 11:00 to 02:00 pm to noon and 04:00 to 06:00 pm for the afternoon. From the results of the survey will be calculated and analyzed so that it will acquire the capacity and degree of saturation. The degree of saturation can be used as an indicator of the performance of a road segment. Where the degree of saturation can directly determine the performance of a road. Under Indonesian Highway Capacity Manual for urban roads in 1997, requires the degree of saturation is not exceeded 0.85. Based on the results obtained penilitian the degree of saturation at the Khatulistiwa Road segment that is the intersection of 0.929 and Suwignyo  Road is 0.441 ,  Husein Hamzah Road is 0546, Martadinata Road is 0.564, H. Rais. A. Rahman Road is 0.726, and the intersection of Putri Candramidi Road is 0.512, Sultan Syarif Abdurrahman Road is 0.749, Sultan Syahrir is 0.625. For Sultan Syarif Abdurrahman Road with the degree of saturation 0.749 at rush hour in a stalemate but at certain hours of traffic flow on these roads smoothly. So to overcome gived one alternative solution, adding the width of road segments and intersections that are experiencing congestion and curb all obstacles aside so reduce conflicts that can lead to congestion.    Keywords : Capacity, degree of saturation, level of performance, congestion, traffic